A patient with MELAS syndrome combined with autoimmune abnormalities: a case report - Zhao, Mingmin; Zuo, Chun; Hao, Hongyu; Xing, Xing; Zhao, Lei; Li, Na (Frontiers in Neurology, 2023)
Background Mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes (MELAS) is a group of maternally inherited disorders caused by mutations or deletions in mitochondrial genes with mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes as the main clinical manifestations. Case presentation We reported a 20-year-old female patient with MELAS syndrome combined with autoimmune abnormalities. She suffered from an intermittent headache in the right temporal region with no obvious cause, and then, after strenuous exercise in dance class, the headache became aggravated, accompanied by unresponsiveness, blurred vision, and diplopia. Her blood lactate levels were elevated, her antinuclear antibodies were positive, and the antimetabolic glutamate receptors 5 in her serum were positive. Brain DWI showed a hypertensive signal in the right temporo-parietal-occipital cortex and subcortical area. Brain MRS showed decreased NAA peak and increased Lac peak. Muscle biopsy showed myogenic damage, and the modified Gomori trichrome (MGT) staining showed ragged red fibers (RRF). A genetic study revealed a mitochondrial DNA A3243G mutation. Conclusion Mitochondrial encephalomyopathy is a rare clinical condition; however, the association with autoimmune diseases is not yet clear and still needs further research and analysis.